Deep Dive into South Korea's Corporate Economy: Evolution, Dynamics, and Future Prospects (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article offers a comprehensive analysis of South Korea's corporate economy, tracing its evolution from the rapid industrialization era to its current high-tech and innovation-driven market. It examines the foundational role of chaebols, their influence on economic policies, and the dynamic interaction between large conglomerates and small to medium-sized enterprises (SMEs). Key focuses include the impact of corporate governance reforms, the integration of advanced technologies within corporate strategies, and the effects of global economic shifts on domestic corporate practices. Additionally, the study discusses the growing importance of corporate social responsibility and sustainability. The article concludes with strategic forecasts and implications for future corporate development in South Korea, providing valuable insights for stakeholders navigating this vibrant economic landscape.